Fungal treatment of metoprolol and its recalcitrant metabolite metoprolol acid in hospital wastewater: Biotransformation, sorption and ecotoxicological impact. (1st April 2019) - Jaén-Gil, Adrián; Castellet-Rovira, Francesc; Llorca, Marta; Villagrasa, Marta; Sarrà, Montserrat; Rodríguez-Mozaz, Sara; Barceló, Damià
Abstract: Hospital wastewater (HWW) effluents represent an important source of contaminants such as pharmaceutical compounds and their human metabolites. To better evaluate dedicated treatment of hospital effluents for pollutant mitigation, not only the parent compounds should be considered but also the intermediates generated during treatment. The metabolite metoprolol acid (MTPA) has been found in urban wastewaters at higher concentration than its parent compound metoprolol (MTP), being more recalcitrant to biodegradation. The aim of this study was to investigate degradation, transformation and sorption of the β-blocker MTP, and its recalcitrant metabolite MTPA, during water treatment based on the fungi Ganoderma lucidum, Trametes versicolor and Pleurotus ostreatus . Fourteen intermediates were identified in MTP biotransformation while five of them also attributed to MTPA biodegradation and two to MTPA only. Their identification allowed their correlation in separate biotransformation pathways suggested. The highest degradation rate of metoprolol (up to 51%) and metoprolol acid (almost 77%) was found after 15-days treatment with Ganoderma lucidum, with an increase in toxicity up to 29% and 4%, respectively. This fungus was further selected for treating real HWW in a batch fluidized bed bioreactor (FBB). Treated wastewater and fungal biomass samples were used to evaluate the distribution of the target compounds and the intermediates identified between solid and liquid phases. While similar elimination capabilities were observed for the removal of metoprolol, and even higher for its persistent metabolite metoprolol acid, the extent on compound transformation diminished considerably compared with the study treating purified water: a high level of the persistent α-HMTP and TP240 were still present in effluent samples (15% and 6%, respectively), being both TPs present at high proportion (up to 28%) in fungal biomass. This is the first time that pharmaceutical TPs have been investigated in the fungal biomass. Graphical abstract: Image 1 Highlights: Degradation, transformation and sorption of MTP and MTPA in fungal treatment. Satisfactory elimination of the recalcitrant metabolite MTPA, up to 77%. Tentative identification of 16 TPs from MTP and MTPA biotransformation. G. lucidum treating hospital wastewater in an aerobic fluidized bed bioreactor. Distribution of TPs between hospital wastewater and fungal biomass phases.